Development of Qur’an Hadis Curriculum at MIN 2 South Tangerang City - Robiatul Adawiyah; Nanda Nadhira; Muhammad Zuhdi (al-Afkar, Journal For Islamic Studies, 2026)
In the education system, the curriculum is an important component. The change in the national curriculum, namely to the Independent Curriculum, presents its own challenges in its implementation. MIN 2 South Tangerang City is one of the madrasas that fully implements the Independent Curriculum by developing the curriculum, including the development of the Qur'an and Hadith curriculum. Therefore, the purpose of this study is to analyze the development of the Qur'an and Hadith curriculum at MIN 2 South Tangerang City, with the formulation of the problem being how the development of the Qur'an and Hadith curriculum at MIN 2 South Tangerang City. This study uses a qualitative method with the type of research being a field study. Data were collected through observation, documentation, and in-depth interviews. The data obtained were then analyzed using Miles Huberman's qualitative analysis technique. The results of the study indicate that MIN 2 South Tangerang City has successfully developed the Qur'an and Hadith curriculum through the development of the Madrasah Operational Curriculum (KOM), which it carried out, taking into account the stages of planning, implementation, and evaluation. Thus, MIN 2 South Tangerang City can be an inspiring model for other schools, especially madrasas, in responding to educational challenges through curriculum development.